Pengaruh Profesionalisme, Disiplin Kerja dan Motivasi Kerja terhadap Kinerja Satuan Polisi Pamong Praja (Satpol PP) Di Kecamatan Pademangan - Sukimin; Muhammad Firzah (Reformasi Administrasi, 2026)
Nowadays, people's lives have undergone many changes as a result of the progress that has been achieved in the previous development process and the rapid progress in science and technology. The changes that can be felt now are the changes in people's mindsets towards being more critical. This is possible because every day the community is getting smarter and increasingly understands their rights and obligations as citizens. Such community conditions demand the presence of a government that is able to meet various demands of needs in all aspects of their lives. This study aims to determine the effect of professionalism. The work discipline of employees and their work motivation on improving the performance of Satpol PP. The population in this study were 60 members of Satpol PP in Pademangan District. Using a saturated sample technique with a negative Likert scale technique with an interval of 5. Data analysis techniques with multiple linear regression. The conclusion of this study is that professionalism, work discipline and motivation have a positive effect on the dependent variable (Y) Performance. And professionalism, work discipline and motivation simultaneously affect the performance (Y) of the Civil Service Police Unit (Satpol PP) in Pademangan District